ANALISIS KEMAMPUAN INTERAKSI SOSIAL KELAS RENDAH SDN PATIKIDUL 01 - Kusumawati, Putri Ika; Purbasari, Imaniar; Najikhah, Fatikhatun (STKIP Persada Khatulistiwa Sintang, 2026)
This study aimed to examine social interaction among lower-grade students at SDN Patikidul 01. The research employed a qualitative narrative approach, with data collected through interviews, observations, and documentation. The subjects consisted of six students selected from a total of 32 students in Class I.C, along with the classroom teacher. The results indicated that students’ social interaction skills were generally in the good category, as they were able to interact effectively with peers and teachers. Among the students who initially exhibited introverted tendencies, two out of three showed improvement in their social interactions after the teacher implemented a seating arrangement strategy. The findings suggest that social interaction skills are influenced not only by internal factors but also by external factors such as the learning environment. In conclusion, this study highlights the importance of supportive classroom strategies in enhancing students’ social interaction skills. The results can serve as a reference for teachers in developing effective approaches to improve social interaction among lower-grade elementary students.